Practical Fitness Testing : Analysis in Exercise and Sport. - Coulson, Morc (Fitness Professionals Ser., 2011)
An indispensible guide for anyone involved in prescribing exercise programmes for clients or groups. Effective fitness tests are crucial to measure current fitness and then monitor progress to check the effectiveness of training. Includes both the theory and pratice of fitness testing in fitness and sports settings.